Kajian Sosial Ekonomi Rencana Pembangunan Jembatan Selat Malaka (JSM) - Kusumartono, FX Hermawan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
Plan of infrastructure development of The Strait of Malaka bridge, which will connect the island of Sumatra and Malaysia, has been previously done, either by Indonesia goverment and also Malaysia goverment. Development of this bridge expected economic movement fluent from Malaysia to Indonesia and conversely. Also by built this bridge will support Asia road-works and ASEAN highway, which one of them is connecting Malaysia and Indonesia. To support the plan is required is exsitence of an initial research from social, economics, security and policy aspect.Research method applied is two methods at the same time that is quantitative and qualitative. The metodologies to be used in this research are both quantitative and qualitative. This research is the explorative one with the characteristic for finding out problems ins stakeholders which never been clearly. Result of research is got, that needing existence readiness of the Goverment of Indonesia, either social, economics, policy and security aspect before developmnet of The Strait of Malaka bridge is realized.